A laboratory study of the impact of ultraconservative access cavities and minimal root canal tapers on the ability to shape canals in extracted mandibular molars and their fracture resistance. (21st September 2020) - Augusto, C. M.; Barbosa, A. F. A.; Guimarães, C. C.; Lima, C. O.; Ferreira, C. M.; Sassone, L. M.; Silva, E. J. N. L.
Abstract: Aim: To evaluate the influence of ultraconservative endodontic access cavities (UEC) and the use of instruments with various tapers (.03 or .05) and tip diameters (25 or 40) on the ability to shape canals in mandibular molars and their fracture resistance in comparison with traditional endodontic access cavities (TEC). Methodology: Thirty‐two intact extracted mandibular molars were scanned in a micro‐computed tomography device, matched based on similar anatomical features and assigned to UEC or TEC groups and to subgroups according to mechanical canal preparation with Bassi Logic™ rotary NiTi instruments with .03 or .05 taper ( n = 8 per group). The teeth were mounted onto a mannequin head, and the pulp chambers were accessed and the root canals subjected to instrumentation. In the first stage, size 25 endodontic instruments were used, with .03 or .05 tapers. The teeth were re‐scanned. Subsequently, a second canal instrumentation was performed with the size 40 instruments with .03 or .05 tapers and scanned again. The root canals were filled and then the teeth restored before being subjected to fracture resistance tests. The data on untouched canal areas, canal transportation, centring ability, the percentage of removed dentine and maximum load at fracture were analysed. One‐way anova and Tukey's tests were performed for inter‐group analysis. The paired‐samples t‐test was performed on the results between size 25 and size 40 apical preparations for each individual specimen ( P < 0.05). Results: No significant difference was observed for the percentage of untouched canal area when comparing UEC and TEC groups or between the .03 and .05 tapers with the same instrument tip size ( P > 0.05). There was a significantly lower percentage of untouched canal area after instrumentation with size 40 instruments when compared to size 25 ( P < 0.05). No significant difference in the percentage of dentine removed was observed between the access cavities or the different tapers ( P > 0.05). Size 40 apical preparations removed significantly more dentine than size 25 preparations ( P < 0.05). No significant differences were observed in canal transportation, centring ability and fracture resistance in any of the tested groups ( P > 0.05). Conclusions: Ultraconservative endodontic access cavities did not offer any advantages in comparison with traditional endodontic access cavities on the ability to shape canals, nor the fracture resistance of mandibular molars. No differences were observed in shaping ability and fracture resistance between .03 and .05 taper canal preparations. Apical preparation with larger instruments resulted in significantly less untouched canal area in all groups.